We the People and We the States: Liberalism and Republicanism in Antifederalist Amendments - Skees, Allison (Kansas State University. Dept. of History, 2012)
The Bill of Rights has been enshrined with the Constitution as one of the United States’ fundamental documents and safeguards of liberty. The Antifederalists, opponents of the Constitution, were the first people to demand amendments to the Constitution and call specifically for a bill of rights. The bill of rights that was adopted represents only a fraction of the amendments Antifederalists wanted. An examination of the speeches, letters and pamphlets of Antifederalists in Pennsylvania, Massachusetts, Virginia and New York and the documents from the ratifying conventions of these four states reveals the surprising number and variety of the Antifederalists’ proposed amendments. The Antifederalists’ theories about fundamental rights and the combination individual and states’ rights in the amendments they wanted demonstrate the influence of two political philosophies: Lockean liberalism and republicanism. The influence of two seemingly contradictory ideologies in Antifederalist thought raises questions about the dominance and compatibility of political philosophy in the revolutionary period. In addition the examination of proposed Antifederalist amendments reemphasizes the level of conflict and division that challenged the founding generation in the early republic.
Keywords: Antifederalism; Liberalism; Republicanism; Constitutional amendments